Application of the Technique of Extracorporeal Membrane Oxygenation in a Patient With Respiratory Distress Syndrome Associated With Myasthenia Gravis - N. M. Kruglyakov; D. G. Levitova; G. I. Bagzhanov; K. K. Gubarev; S. S. Ochkin; O. V. Parinov; S. S. Petrikov; K. A. Popugaev; A. S. Samoilov (Неотложная медицинская помощь, 2021)
Myasthenia gravis is an autoimmune neuromuscular disease characterized by pathologically rapid fatigue of striated muscles [1]. The main symptom of myasthenia gravis is the presence of pathological muscle weakness with involvement of the ocular, bulbar and skeletal muscles in the pathological process. The provoking factors for the development of myasthenia gravis can be infectious diseases, surgery, drugs [2, 3]. The main danger is represented by myasthenic and cholinergic crises, which are characterized by a severe course and high mortality; therefore, the problems of treating myasthenia gravis are still of high medical and social significance. The prevalence of myasthenia gravis is 17.5–20.3 per 100 thousand population, and the number of patients is increasing by 5–10% annually [4, 5]. In recent years, there has been a steady increase in morbidity with an increase in age over 50 years [6, 7]. Myasthenia gravis is a serious disease with a high mortality rate of up to 30–40% [3]. There are difficulties in the early differential diagnosis of muscle weakness in patients with respiratory failure between myasthenia gravis, myasthenic syndrome and critical illness polyneuropathy. These difficulties and insufficient awareness of patients and doctors of various specialties about myasthenia gravis can lead to the choice of the wrong treatment tactics and the development of myasthenic crisis, which is manifested by respiratory failure, requiring respiratory support. The progression of respiratory failure against the background of myasthenic crisis may require the use of extracorporeal membrane oxygenation (ECMO).It is necessary to expand the differential diagnosis of muscle weakness in a patient during the period of resolution of respiratory failure, allowing to move away from compulsory respiratory support, termination of ECMO.